2019
DOI: 10.11113/mjfas.v14n4.1072
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chilling injury and internal browning condition on quality attributes, phenolic content, and antioxidant capacity during sub-optimal cold storage of malaysian cultivar pineapples

Abstract: Pineapple cold storage at sub-optimal temperature (4 ± 2 °C) and duration of storage (0, 7, 14, 21, and 28 days) was periodically tracked to investigate its effect on physical injuries known as chilling injury (CI) and internal browning (IB), which contribute to degradation of pineapple’s quality attributes (i.e., pH, total soluble solids (TSS) concentration, ascorbic acid (AA) content, ion leakage (EL), antioxidant capacity, and total phenolic content (TPC). In this study, three main Malaysian pineapple culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The pineapple processing generated 45-65% residues, consisting of pulp, peels, stems and leaves. Consequently, various studies have reported the chemical composition of various pineapple varieties (Correia et al, 2007;Hemalatha & Anbuselvi, 2013;Rani & Nand, 2004), including the nutritional value (De Ancos et al, 2016;Hemalatha and Anbuselvi, 2013), volatile compounds (Dolhaji et al, 2018;Lasekan & Hussein, 2018;Pino, 2013), antioxidants (Ali et al, 2020;Dolhaji et al, 2018) and fibres (Asim et al, 2015). Notably, the substantial nutritional composition in pineapple waste has made the by-product a promising raw material in the animal feed industry.…”
Section: Nutritional Composition Of Pineapple Wastementioning
confidence: 99%
See 1 more Smart Citation
“…The pineapple processing generated 45-65% residues, consisting of pulp, peels, stems and leaves. Consequently, various studies have reported the chemical composition of various pineapple varieties (Correia et al, 2007;Hemalatha & Anbuselvi, 2013;Rani & Nand, 2004), including the nutritional value (De Ancos et al, 2016;Hemalatha and Anbuselvi, 2013), volatile compounds (Dolhaji et al, 2018;Lasekan & Hussein, 2018;Pino, 2013), antioxidants (Ali et al, 2020;Dolhaji et al, 2018) and fibres (Asim et al, 2015). Notably, the substantial nutritional composition in pineapple waste has made the by-product a promising raw material in the animal feed industry.…”
Section: Nutritional Composition Of Pineapple Wastementioning
confidence: 99%
“…Moreover, pineapple waste has low ash content (0.04 %) compared to pineapple pulp (1.8%) (Hemalatha and Anbuselvi (2013). A study has identified the volatile and non-volatile compounds responsible for the sweet flavour of six pineapple varieties (Moris, Maspine, MD2, N36, Josapine and Sarawak) grown in Malaysia (Dolhaji et al, 2018;Lasekan & Hussein, 2018) Meanwhile, another study investigated the (Lasekan and Hussein, 2018) volatile aromatic compounds in the Shenwan pineapple (Wei et al, 2014).…”
Section: Nutritional Composition Of Pineapple Wastementioning
confidence: 99%
“…Storage temperature affects the shelf life of pineapples. Storing pineapples at low temperatures can delay yellowing of the skin and freshness of the fruit, extending the shelf life of the fruit [1]. 'MD2', 'Josapine', and 'Morris' pineapple cultivars have a storage temperature of 10 ºC to prolong shelf life [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 Symbols of clone (A1: 'GP3' and A2: 'MD2'), decrowning (B1: crown and B2: crownless), and coating (C1: H2O, C2: chitosan 1%, C3: ABA+chitosan mix, C4: ABA 50 mg/L). Lowercase letters indicate statistically ignificant difference by DMRT (p≤0.05).…”
mentioning
confidence: 99%